2022
DOI: 10.1080/14413523.2022.2127179
|View full text |Cite
|
Sign up to set email alerts
|

Rage against the machine: investigating conspiracy theories about the video assistant referee on Twitter during the 2018 FIFA World Cup

Abstract: The 2018 edition has been watched by more than 3.5 billion people (FIFA, 2018a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…With regard to fans, VAR is an emotion transfer object, which also affects VAR satisfaction. In Bertin et al (2023)'s study, it was also noted that negative tweets on VAR increased at the end of the group stage, which may be related to the elimination of the team, and the fans expressed negative emotions on VAR to rationalize the situation of the team and maintain the image of the team.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to fans, VAR is an emotion transfer object, which also affects VAR satisfaction. In Bertin et al (2023)'s study, it was also noted that negative tweets on VAR increased at the end of the group stage, which may be related to the elimination of the team, and the fans expressed negative emotions on VAR to rationalize the situation of the team and maintain the image of the team.…”
Section: Discussionmentioning
confidence: 98%
“…The questionnaire is issued to Chinese fans, and the teams participating in the World Cup are mostly distributed in various countries; therefore, the satisfaction of fans in different countries and regions with the World Cup VAR can be compared. In addition, some studies have indicated that the utilization of VAR in crucial moments of the game has an impact on match results (Kolbinger and Knopp, 2020;Bertin et al, 2023), and that the number of tweets on negative emotions associated with VAR increases. Therefore, more variables can be added to future research on fan satisfaction with VAR.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Specific conspiracy belief items are often event-specific but not group-specific (i.e., they remain vague and generic regarding the conspiring groups). However, conspiracy theories regarding a given event can vary in the perpetrating groups portrayed (e.g., see Bertin, Delouvée, et al, 2023, in the context of the 2018 FIFA World Cup). Methodologically, while the event to which a conspiracy belief scale refers is established by the researcher, the plotting group can hardly be set a priori but depends on the characteristics of the participants (e.g., worldview, political orientation, demographics).…”
Section: Methodsmentioning
confidence: 99%
“…Specific conspiracy belief items are often eventspecific but not group-specific (i.e., they remain vague and generic regarding the conspiring groups). However, conspiracy theories regarding a given event can vary in the perpetrating groups portrayed (e.g., see Bertin et al, 2022, in the context of the 2018 FIFA World Cup).…”
Section: Methodsmentioning
confidence: 99%